1967
DOI: 10.1002/pol.1967.160050212
|View full text |Cite
|
Sign up to set email alerts
|

Study of crystallization kinetics of trans‐1,4‐polyisoprene

Abstract: The concentrations and the growth rates of high‐ and low‐melting type spherulites of trans‐1,4‐polyisoprene were measured in the temperature range 39–49°C. It was shown that above about 40°C., the crystallization rate of trans‐1,4‐polyisoprene is determined primarily by the radial growth rate of high‐melting form (HMF) spherulites, whereas the predominance of the low‐melting form (LMF) crystals below 40°C. can be attributed to the high rate of formation of LMF primary nuclei at lower crystallization temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…17,18 trans-1,4-polyisoprene (TPI; gutta percha) was also reported to exhibit the solid-state transition from the b form to the a form by heating, [19][20][21] but this observation has yet to be confirmed. [22][23][24][25] A similar situation might exist for the other types of crystalline polymers.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…17,18 trans-1,4-polyisoprene (TPI; gutta percha) was also reported to exhibit the solid-state transition from the b form to the a form by heating, [19][20][21] but this observation has yet to be confirmed. [22][23][24][25] A similar situation might exist for the other types of crystalline polymers.…”
Section: Introductionmentioning
confidence: 84%
“…Some reports proposed that the b-form transforms to the a-form directly (solid-to-solid transition), [19][20][21] but other reports proposed another possible phasetransformation mechanism involving the melting of the b form followed by the recrystallization into the a form in a higher temperature region (melt-recrystallization). [22][23][24][25] Determining the correct phase-transition mechanism for both PVDF and TPI may reveal a new aspect regarding the phase transition of polymers occurring near the melting region and may thereby become an important trigger to reinvestigate the phase-transition behaviors proposed for many crystalline polymers from a different point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The aand b-forms of TPI crystals are often called the high-melting crystal form (HMF) and low-melting crystal form (LMF), respectively. 3 The HMF is obtained by slowcooling from the melt, whereas the LMF is obtained by rapid-cooling, or quenching, from the melt. The fundamental properties of TPI, such as crystal morphology or crystallization behavior, have been studied by Davies and Long 4,5 However, the properties of TPI composites containing additives have been comparatively less wellstudied.…”
Section: Introductionmentioning
confidence: 99%
“…However, the structural information, which is fundamentally important to study the microscopically viewed crystallization phenomenon, has not been well established. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] To further develop this polymer in the recent field of green polymer science, we need to clarify the structural information in detail.…”
Section: Introductionmentioning
confidence: 99%
“…21,[25][26][27][28][29] For example, Cooper and Vaughan 29 measured the dilatometry in the isothermal crystallization and estimated the Avrami index, and Fischer and Henderson 21 studied the formation of spherulites from the melt using a polarized optical microscope. However, the study of crystallization viewed from the molecular level has not been reported.…”
Section: Introductionmentioning
confidence: 99%